(untitled) (Baghdad Science Journal, 2011)
The wild populations of the vinegar fly Drosophila melanogaster Meigen from two regions in Baghdad , Saidiya and Tuwaitha were selected for this study to investigating the frequency of the dominant lethality , this parameter was investigated through fecundity and egg hatchability rate which considered as main indicator for the presence of mutation . The results showed that fecundity rate in Saidiya increased with time , so the lowest rate was 65.5 eggs per female in November and the highest was 87.4 eggs in May , the same results was observed for Tuwaitha except a significantly decrease in fecundity rate that was observed in May which was 42.7 eggs , as well as another significant differences between the two regions was observed in March when the rate was in Saidiya more than Tuwaitha . The hatchability rate increased gradually in Saidiya until March which equal 69.3% , then decreased significantly in May and reached 48.6% , meanwhile , in Tuwaitha the highest hatchability rate was 67.6% in November, then it was decreased until March , while in May it decreased significantly to 24.5% . So , the hatchability rate decreased significantly in Tuwaitha if compared with that of Saidiya in March and May , before that , the opposite was in November and there isn’t any significant differences between the two regions in January .